Answer:
da answer iz two cause wen u add one plus one u get answer two
Step-by-step explanation:
let mi hope dat it useful
Help me and I’ll help you
{-2,12} -D because 12x divided by 24 is -2 and 10x plus 2x is 12
Answer:
c) (
d) (
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given that the binomial expression
(
Multiply
( 36 + 6√12 -6√12 -(√12)²)
= ( 36 -12)
= 24
c) (
<u><em>Step(ii):- </em></u>
Given that the binomial expression
(
Multiply
= 9 - 3√8 + 3√8 -(√8)²
= 9 - 8
= 1
d) (
Answer:
B² - 4AC < 0
Step-by-step explanation:
Check for:
B² - 4AC
The equations for which
B² - 4AC < 0
have complex roots
For A, B and C, use this form of the quadratic:
Ax² + Bx + C = 0